Brucella Rough Mutant Induce Macrophage Death via Activating IRE1α Pathway of Endoplasmic Reticulum Stress by Enhanced T4SS Secretion - Li, Peng; Tian, Mingxing; Bao, Yanqing; Hu, Hai; Liu, Jiameng; Yin, Yi; Ding, Chan; Wang, Shaohui; Yu, Shengqing (Frontiers in Cellular and Infection Microbiology, 2017)
Brucella is a Gram-negative facultative intracellular pathogen that causes the worldwide zoonosis, known as brucellosis. Brucella virulence relies mostly on its ability to invade and replicate within phagocytic cells. The type IV secretion system (T4SS) and lipopolysaccharide are two major Brucella virulence factors. Brucella rough mutants reportedly induce the death of infected macrophages, which is T4SS dependent. However, the underlying molecular mechanism remains unclear. In this study, the T4SS secretion capacities of Brucella rough mutant and its smooth wild-type strain were comparatively investigated, by constructing the firefly luciferase fused T4SS effector, BPE123 and VceC. In addition, quantitative real-time PCR and western blotting were used to analyze the T4SS expression. The results showed that T4SS expression and secretion were enhanced significantly in the Brucella rough mutant. We also found that the activity of the T4SS virB operon promoter was notably increased in the Brucella rough mutant, which depends on quorum sensing-related regulators of VjbR upregulation. Cell infection and cell death assays revealed that deletion of vjbR in the Brucella rough mutant absolutely abolished cytotoxicity within macrophages by downregulating T4SS expression. This suggests that up-regulation of T4SS promoted by VjbR in rough mutant ΔrfbE contribute to macrophage death. In addition, we found that the Brucella rough mutant induce macrophage death via activating IRE1α pathway of endoplasmic reticulum stress. Taken together, our study provide evidence that in comparison to the Brucella smooth wild-type strain, VjbR upregulation in the Brucella rough mutant increases transcription of the virB operon, resulting in overexpression of the T4SS gene, accompanied by the over-secretion of effecter proteins, thereby causing the death of infected macrophages via activating IRE1α pathway of endoplasmic reticulum stress, suggesting novel insights into the molecular mechanisms associated with Brucella rough mutant-induced macrophage cytotoxicity.